"Socio-educational factors influencing cultural exchange in teaching English as a second language” - González Mejía, Erika Johanna (2022)
Cultural knowledge is fundamental in foreign language acquisition, allowing students to properly manage and develop the four language skills during the English teaching-learning process as a second language. According to diverse authors, several factors influence the foreign language learning process, which affects students during its acquisition. The present research objective was to determine the socio-educational factors that influence cultural exchange in the teaching-learning of English as a second language as a mechanism for interaction and familiarization in the students of the 2nd semester "A" of the Pedagogy of National and Foreign Languages career at the Technical University of Cotopaxi. The type of research was theoretical-exploratory because a bibliographic review of several authors was carried out to support the research; it was exploratory because the study was limited in this knowledge area, which made it an innovative project in the educational environment. The data collection resource was the survey applied to the selected sample of 36 students of the 2nd semester "A". The analysis of the data determined that learning culture was substantial in language learning. However, the students established that the family and the university environment were the socio-educational factors that most influence cultural knowledge acquisition. The study concluded that culture teaching was not prevalent in English language learning. Therefore, it will be essential that teachers use digital tools and implement activities that facilitate cultural teaching in the educational environment.